Los costos que incurren los pequeños distribuidores de productos lácteos en la ciudad de Quito, de los cuales se ven beneficiadas las grandes empresas de la industria láctea. - Cabezas Cajas, Paulina Fernanda (2016)
Dairies within the production process used for the marketing of their products " distributors " which are small independent entrepreneurs with their own investment have transportation (truck) and capital to start its work to distribute to shops, distributors or business, mainly whole milk, which earn an income , now analyze the costs and investments made by small distributors of dairy products that are benefits for industries. This research is a bibliographical compilation, moving to a field research to understand the perception and reality main data distributors, to finally conclude with an economic analysis to assess the problems presented.